2008
DOI: 10.1159/000115637
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Histamine versus Topiramate in Migraine Prophylaxis: A Double-Blind Study

Abstract: Background: Histamine has a selective affinity for H3 receptors and it may specifically inhibit the neurogenic edema response involved in migraine pathophysiology. Objective: To evaluate the therapeutic potential of subcutaneous administration of histamine in migraine prophylaxis, compared with oral administration of topiramate. Methods: Ninety patients with migraine were selected in a 12-week double-blind controlled clinical trial to evaluate the efficacy of subcutaneous administration of histamine (1–10 ng t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
(29 reference statements)
0
21
0
Order By: Relevance
“…With regard to treatments, limited evidence exists that symptomatic medication, such as Sumatriptan [42, 47], Naproxen Sodium [42] Zolmitriptan [54] and Eletriptan [48] have an impact on disability reduction. Strong evidence is instead reported by studies documenting improvements due to prophylactic medication such as Topiramate [32, 43, 49, 55, 56], Botulinum Toxin type A [33], subcutaneous histamine [56], beta-blockers such as Nebivolol and Metoprolol [50] and Amitriptyline [43]. Limited evidence is available for the effect of pain reduction, achieved through physical exercise, on disability reduction [57].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to treatments, limited evidence exists that symptomatic medication, such as Sumatriptan [42, 47], Naproxen Sodium [42] Zolmitriptan [54] and Eletriptan [48] have an impact on disability reduction. Strong evidence is instead reported by studies documenting improvements due to prophylactic medication such as Topiramate [32, 43, 49, 55, 56], Botulinum Toxin type A [33], subcutaneous histamine [56], beta-blockers such as Nebivolol and Metoprolol [50] and Amitriptyline [43]. Limited evidence is available for the effect of pain reduction, achieved through physical exercise, on disability reduction [57].…”
Section: Resultsmentioning
confidence: 99%
“…Topiramate 100 mg/day was compared with histamine (1-10 ng 2 times/week SC), and both active treatments showed improvement over baseline measures for attack frequency, intensity, and use of rescue medication. 7 Eleven percent (5/45) of subjects treated with histamine withdrew from the histamine group because they were not satisfied with the speed of results, although no AEs were reported. Few subjects reported transitory burning and itching at the injection site.…”
Section: Analysis Of Evidencementioning
confidence: 97%
“…There have been eleven studies since the 2000 guidelines reporting efficacy of topiramate in migraine prevention 3234. One Class I placebo-controlled study showed a lower 28-day frequency of migraine headaches versus placebo (3.31 versus 3.81).…”
Section: Preventive Medications For Migraine: Updatementioning
confidence: 99%